2015
DOI: 10.1039/c5nr02337h
|View full text |Cite
|
Sign up to set email alerts
|

Few layered MoS2lithography with an AFM tip: description of the technique and nanospectroscopy investigations

Abstract: A novel technique to lithograph the MoS2 surface is described here. Mechanically exfoliated MoS2 flakes have been patterned with an atomic force microscope tip. After the patterning process, the lithographed areas have been removed by selective chemical etching. The electronic properties of the MoS2 flakes have been analyzed with spatially resolved photoelectron spectroscopy, with tunable incident photon energy, provided by a synchrotron light source. Tens of meV core level shifts can be recorded in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Surface roughness of less than 0.5 nm in the height profile indicates that the thinning approach of using argon plasma does not destroy its crystallinity and that few of PtTe 2 traces are left in the surface. We note that similar approach has been applied for bulk samples with weak interlayer interaction to obtain thin flakes, such as MoS 2 layer thinning with a local anodic oxidation method . Different from prior works, we modified IBE instrument to speed up argon plasma and successfully thinned as‐grown PtTe 2 with strong interlayer interaction down to atomically thin crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Surface roughness of less than 0.5 nm in the height profile indicates that the thinning approach of using argon plasma does not destroy its crystallinity and that few of PtTe 2 traces are left in the surface. We note that similar approach has been applied for bulk samples with weak interlayer interaction to obtain thin flakes, such as MoS 2 layer thinning with a local anodic oxidation method . Different from prior works, we modified IBE instrument to speed up argon plasma and successfully thinned as‐grown PtTe 2 with strong interlayer interaction down to atomically thin crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that interior oxidation is completely lacking; this absence of oxidation can be explained by reduced interior defects due to graphene (Figure f). The charges or dipoles in the Si substrate generate electric fields on the SiO 2 surface, which reinforce the adsorbate–TMD interaction by inducing an electronic charge transfer, affecting the rate of WS 2 oxidation . However, the oxidation of WS 2 on a graphene/SiO 2 substrate is significantly suppressed, since the transferred graphene covering the SiO 2 screens the surface electric field.…”
mentioning
confidence: 99%
“…This kind of feature reminds of the oxide growth on silicon and on certain polymers caused by a nano-explosion followed by a shockwave (Figure 7) [30]. It is worthy to mention that by means of applying a voltage with an AFM tip on the semiconducting TMDCs MoS2 [31] and WSe2 [32], different types of structures have been achieved, that also resemble the patterns presented in this work. However in both cases, authors highlight the non-oxide nature of the motifs, against the results observed by us that prove the oxide nature of the obtained patterns on above mentioned metallic TMDCs (i.e.…”
Section: Lon On Other Tmdcsmentioning
confidence: 79%